Post abortion counseling and contraception. - Huamán, Moisés (2015)
It is estimated that worldwide 150 million pregnancies occur each year, causing a risk of death to the differing substantially amdre living standards of each population. Thus, in Africa, a woman dies every 24 pregnancies in Latin America and one for every 90 in developed countries one per 1750 pregnancies. It is impossible to know the exact number of abortions, especially the huge underreporting of the more obvious induced abortions in countries that criminalize this procedure; but QE is calculated annually about 60 million induce abortions is worldwide; of these, 3.5 million occur in Latin America